Groovy science : knowledge, innovation, and American counterculture - Kaiser, David; McCray, Patrick (W. Patrick) (The University of Chicago Press, 2016)
In his 1969 book The Making of a Counterculture, Theodore Roszak described the youth of the late 1960s as fleeing science "as if from a place inhabited by plague," and even seeking "subversion of the scientific worldview" itself. Roszak's view has come to be our own: when we think of the youth movement of the 1960s and early 1970s, we think of a movement that was explicitly anti-scientific in its embrace of alternative spiritualities and communal living. Such a view is far too simple, ignoring the diverse ways in which the era's countercultures expressed enthusiasm for and involved themselves in science--of a certain type. Rejecting hulking, militarized technical projects like Cold War missiles and mainframes, Boomers and hippies sought a science that was both small-scale and big-picture, as exemplified by the annual workshops on quantum physics at the Esalen Institute in Big Sur, or Timothy Leary's championing of space exploration as the ultimate "high." Groovy Science explores the experimentation and eclecticism that marked countercultural science and technology during one of the most colorful periods of American history.